A 400, 000 years old milestone of the Acheulian technocomplex in Central-Western France at Londigny (Charente). (April 2020) - Connet, Nelly; Soriano, Sylvain; Bertran, Pascal; Lhomme, Vincent; Debenham, Nick
Highlights: Technological analysis of an unpublished Acheulian assemblage from Western-Central France. Londigny could be one of the southernmost of the northern Acheulean manifestations. Flake tools with abrupt natural edge is a pattern shared with numerous acheulean sites. The search for backed blanks is a constant at MIS 11 sites. Spatial mobility of handaxes is only partly explained by raw materials quality. Abstract: In this paper, we present the results of a technological analysis of an unpublished Acheulian assemblage from Western-Central France from a preventive excavation at Londigny (Charente). The lithic pieces were found in an archaeological layer preserved at the bottom of the infilling of two karstic depressions on the Jurassic plateau. A large series of handaxes found during gravel quarrying in the Charente river valley and sparse assemblages from karstic cavities south of the large meander formed by the Charente river are amongst the main discoveries dating to the Lower Palaeolithic in Charente. In the Poitou region, Londigny is the first open air Lower Palaeolithic industry TL dated to MIS 11 recovered in a stratigraphic context. Only a handful of sites date to this period in North-West Europe. Our study of this assemblage however allows us to describe in detail the lithic production that is characteristic of the Acheulian technocomplex. Despite of the unusual use of small Jurassic flint nodules, both bifacial shaping and flake production highlight a technical package shared by most of the Acheulian industries at that time from North-West Europe to South-West France. The Londigny site, located in a position between north and south, extends the geographical range of the Acheulian in France.